Green Degreaser, eco-friendly cleaning innovation from collaboration between school pupils and UMPSA - Naqiah, Puaad (UMPSA, 2025)
PEKAN, 30 June 2025 – The eco-friendly cleaning innovation, Green Degreaser, developed through the collaboration of Year 6 pupils from Sekolah Rendah Islam Al-Amin Paya Besar (SRIAAPB), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), and MNR Multitech Sdn. Bhd. has successfully made a significant impact in addressing chemical pollution and supporting environmental sustainability.